2019
DOI: 10.1111/jicd.12413
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the fit of zirconia three‐unit fixed partial dentures fabricated by different impression techniques

Abstract: Aim The aim of the present study was to evaluate the marginal and internal fit of zirconium fixed partial denture using different impression techniques. Methods A Nissin Typodont model, including maxillary central incisor and canine with missing lateral incisor, was selected for the present study. Thirty zirconium frameworks were fabricated following three impression techniques (N = 10), conventional silicone impression (group C), scanned dental impression (group S), and Trios 3 (3Shape) intraoral scanner (gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 21 publications
0
7
0
4
Order By: Relevance
“…Artículo de Revisión / Review Article de disilicato de litio (5,8,13), pero autores como Elsayed y col.10 muestran evidencia que el aumento de óxido de itrio a las coronas para favorecer su translucidez, genera una disminución en la resistencia fl exural, traccional y a la fractura comparable al disilicato de litio, pero superando por mucho las fuerzas masticatorias máximas ejercidas. Otro estudio, enfocado en el sector anterior para evaluar la resistencia en función a vectores de fuerza diferentes concluyó que las coronas monolíticas de disilicato de litio tenían mejores propiedades, en lo que refi ere a resistencia debido al módulo de elasticidad, que las de zirconia con recubrimiento y comparables a las monolíticas (3,19).…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Artículo de Revisión / Review Article de disilicato de litio (5,8,13), pero autores como Elsayed y col.10 muestran evidencia que el aumento de óxido de itrio a las coronas para favorecer su translucidez, genera una disminución en la resistencia fl exural, traccional y a la fractura comparable al disilicato de litio, pero superando por mucho las fuerzas masticatorias máximas ejercidas. Otro estudio, enfocado en el sector anterior para evaluar la resistencia en función a vectores de fuerza diferentes concluyó que las coronas monolíticas de disilicato de litio tenían mejores propiedades, en lo que refi ere a resistencia debido al módulo de elasticidad, que las de zirconia con recubrimiento y comparables a las monolíticas (3,19).…”
Section: Discussionunclassified
“…Si evaluamos a las coronas monolíticas en relación al desgaste (término para describir la pérdida progresiva de la superfi cie de un diente debido a varios factores, excepto la caries dental) (16), que pueden ocasionar a las estructuras antagonistas, encontramos estudios con diversos resultados y conclusiones divergentes por la suma de variables consideradas, básicamente algunos mencionan que va a depender de la metodología del estudio (in vitro/in vivo) (12,18), otros el tipo de antagonista a utilizarse (esmalte, hidroxiapatita reforzada, acero inoxidable, resina acrílica, cerámica, etc.) (9,17), pero al parecer convergen en el punto de que la restauración va a ocasionar mayor desgaste que un antagonista natural (13,16).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Dental literature has reported similar marginal and internal discrepancies of tooth-supported crowns and short span fixed dental prostheses fabricated by using a complete digital workflow compared with conventional methods. 3,5,6,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] A recent systematic review and meta-analysis reported that digital scanning techniques provided a reliable alternative to conventional impression methods for fabricating tooth-supported crowns and FPDs up to 4 units. 31 The majority of the published studies analyzing the fit of tooth-supported crowns or short span FDPs fabricated from intraoral scans did not report the scan extension of the scans performed, [20][21][22][23][24][25] although some studies obtained complete- 26 or half-arch scans, [27][28][29] or used short-span reference casts.…”
Section: Accuracy Of Ioss For Fabricating Tooth-supported Restorationsmentioning
confidence: 99%